Effects of 3DVR-haptic simulation training on cognitive functions: a functional neuroimaging pilot study using swLORETA qEEG - Manchorova, Neshka; Kolev, Dimitar; Kirkova-Bogdanova, Angelina; Simeonov, Nikolay; Stavreva, Elena (Frontiers in Human Neuroscience, 2026)
Introduction and aimTechnological advancements in neuroscience have transformed our understanding of the processes underlying behavior and cognition. The study aims to investigate the changes in functional brain cognitive networks activated by 3DVR haptic-based simulation training in endodontics.Materials and methodsFifteen dental students (7 females and 8 males), mean age 21.5 ± 0.5 years, trained for the first time with a 3DVR-haptic simulator in April 2025, participated in the study. The one-group pretest–postest interventional design was approved by the Ethics Committee of MU–Plovdiv. Before and after a one-hour VR-endodontic access practice, we measured connectivity changes in the 49 Brodmann fields using swLORETA qEEG. Data were standardized using an age-stratified normative base through Z-score calculations. The qEEG recordings were processed by Neuroguide 3.3.7 and statistically analyzed with Navistat, p < 0.05. To control the cognitive effects the participants completed a classic neuropsychological test for assessing executive functions before and after VR training: the Trail Making Test (TMT) Part A and Part B.ResultsThe most significant changes in brain activity were observed in the beta frequency range (18–24 Hz), primarily in the left frontal dorsolateral area, and the left insula and hippocampus. A significant change in activity was found in the mediobasal temporal cortex on both the left and right sides. According to connectomics, the most substantial changes were observed in the structures of 6, 7 and 8 ICN. The TMT data showed significant difference in records of the average time, difference and ratio scores before and after training in VR (p < 0.05).Conclusion3DVR-haptic simulation training in endodontic actively engages cognitive modalities and brain structers related to executive functions, visuospatial sense, attention, and working memory, resilience to stress, and the need for reward. Objective electrophysiological changes correlate with improvements in neuropsychological performance TMT. Despite the limitations of this study, we argue that swLORETA qEEG method is a novel objective approach with a promising potential for validation the effects of 3DVR-haptic simulation training on cognitive functions, offering better temporal resolution compared to fMRI, along with lower costs and safety.